LGG/LAC-MMT combination mitigates AFB1-induced liver and intestinal injury in mice based on intestinal microbiota modulation - Cheng, Jiaxin; Gao, Ying; Lv, Hongming; Li, Jing; Sun, Xudong; An, Tianhui; Liu, Honglin; Wang, Junqi; Zhang, Haifeng; Wang, Haiyan; Zou, Siqi; Fan, Zhao; et al. (Frontiers in Veterinary Science, 2025)
AFB1 induces hepatotoxicity and enterotoxicity. Lactobacillus acidophilus (LAC) and Lactobacillus rhamnosus (LGG), both belonging to LAB, have strong binding affinity for AFB1. Montmorillonite (MMT) not only adsorbs AFB1 but also serves as a carrier for LAB, thereby enhancing their colonization ability and prolonging their survival. Despite the unclear effects of LGG/LAC-MMT combination on AFB1-induced tissue injury and intestinal microbiota disruption, this study aimed to determine whether it could effectively alleviate tissue damage from AFB1 exposure and enhance LAB colonization capacity in mouse intestines. Separately, LGG (2 × 109 cfu/mL) and LAC (2 × 109 cfu/mL) were combined with MMT (0.5 mg/kg), and the AFB1-intoxicated mice were gavaged with the mixtures for 4 weeks. Findings suggested that LGG, LAC, and MMT supplementation restored oxidative stress and inflammatory caused by AFB1 to some degree. Furthermore, they altered the intestinal microbiota structure, enhancing the colonization ability of LABs, thereby alleviating liver and intestinal injury. The combination of LGG/LAC-MMT was more effective, especially LAC-MMT. Overall, LGG/LAC-MMT exhibits a synergistic effect and can effectively ameliorate AFB1-induced tissue injury and intestinal microbiota disorder.